Entrepreneurship Starts in the Classroom: Behavioral Mediation in the Education and Intention - Kartikaningrum, Lina; Andika, Endrik (Journal Business Administration: Entrepreneurship and Creative Industry, 2025)
This study aims to analyze the influence of entrepreneurship education on entrepreneurial intention, with entrepreneurial behavior serving as a mediating variable. Data were collected from 128 students of the Faculty of Economics and Business at the University of PGRI Kanjuruhan Malang using a structured questionnaire. The findings reveal that entrepreneurship education has a significant effect on both entrepreneurial behavior and entrepreneurial intention. Furthermore, entrepreneurial behavior significantly influences entrepreneurial intention. These results support the reinforcement of entrepreneurship curricula in higher education to foster the development of young entrepreneurs within academic environments.